PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan PD BPR BKK Taman Pemalang) - Kusuma, Galan; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2018)
Based on the results of the pre-survey interview with 15 employees of PD BPR BKK Taman Pemalang, there were phenomenon where there were problems of lack of employee motivation in work, lack of supervision by the leader, and the lack of employee participation in following the company's activities so that this research use independent variable that is transformational leadership style, organizational culture and work motivation and dependent variable is employee performance.This research was conducted by the method of distributing questionnaires that have been through the instrument test, then disseminated to 75 respondents in this case is the employee of PD BPR BKK Taman Pemalang lower level. This research uses data alnalisis method such as validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test.The result of analysis shows that the variables of transformational leadership style, work motivation and organizational culture have positive and significant effect on employee performance. The independent variable has an effect of 82.8% on employee performance. While the rest of 17.2% influenced by other factors outside this study.